1973
DOI: 10.2307/1238344
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity Cost of Time and Other Socioeconomic Effects on Away‐From‐Home Food Consumption

Abstract: Viewing the household as both a producing and consuming unit suggests the opportunity cost of the homemaker's time to be an important factor affecting food consumption. Opportunity cost of time is shown empirically to have a positive affect on away‐from‐home consumption for employed homemakers in all 12 region‐urbanization classes studied. The same response is shown for unemployed homemakers in most classes. Furthermore, the estimated bias associated with income elasticities estimated without adjustment for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
7

Year Published

1989
1989
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(70 citation statements)
references
References 3 publications
4
58
0
7
Order By: Relevance
“…Research typically finds that the opportunity cost of time is positively related to income, employment and wages (for example, Prochaska andSchrimper, 1973, andMormorstein et al, 1992) such that we would expect to see this reflected in our empirical findings with regard to our inaccurate reporting equation.…”
Section: Some Possible Motivations For Inaccurate Reportingmentioning
confidence: 66%
“…Research typically finds that the opportunity cost of time is positively related to income, employment and wages (for example, Prochaska andSchrimper, 1973, andMormorstein et al, 1992) such that we would expect to see this reflected in our empirical findings with regard to our inaccurate reporting equation.…”
Section: Some Possible Motivations For Inaccurate Reportingmentioning
confidence: 66%
“…Many studies have found a positive relationship between income and the consumption of FAFH, such as Prochaska and Schrimper (1973), McCracken and Brandt (1987), Yen (1993), Gould and Villarreal (2006) and Bai et al (2010). Higher income households typically spend more on products and services such as leisure, variety, dining facilities (for example waiters), ambience and alcohol service .…”
Section: Influence Of Income On Food-away-from-home Demandmentioning
confidence: 99%
“…McCracken & Brandt, 1987;Mutlu & Gracia, 2006;Prochaska & Schrimper, 1973;Yen, 1993). The basic framework of this model is to maximize a household utility function, subject to the household production function, time constraint and income constraint (Becker, 1965).…”
Section: Theoretical Modelmentioning
confidence: 99%